Functional and Structural Adaptations in the Pancreatic alpha-Cell and Changes in Glucagon Signaling During Protein Malnutrition - Marroqui, Laura; Batista, Thiago M.; Gonzalez, Alejandro; Vieira, Elaine; Rafacho, Alex; Colleta, Simone J. [UNESP]; Taboga, Sebastiao R. [UNESP]; Boschero, Antonio C.; Nadal, Angel; Carneiro, Everardo M.; Quesada, Ivan (Endocrine Soc, 2012)
Chronic malnutrition leads to multiple changes in beta-cell function and peripheral insulin actions to adapt glucose homeostasis to these restricted conditions. However, despite glucose homeostasis also depends on glucagon effects, the role of alpha-cells in malnutrition is largely unknown. Here, we studied alpha-cell function and hepatic glucagon signaling in mice fed with low-protein (LP) or normal-protein diet for 8 wk after weaning. Using confocal microscopy, we found that inhibition of Ca2+ signaling by glucose was impaired in alpha-cells of LP mice. Consistent with these findings, the ability of glucose to inhibit glucagon release in isolated islets was also diminished in LP mice. This altered secretion was not related with changes in either glucagon gene expression or glucagon content. A morphometric analysis showed that alpha-cell mass was significantly increased in malnourished animals, aspect that was probably related with their enhanced plasma glucagon levels. When we analyzed the hepatic function, we observed that the phosphorylation of protein kinase A and cAMP response-binding element protein in response to fasting or exogenous glucagon was impaired in LP mice. Additionally, the up-regulated gene expression in response to fasting observed in the hepatic glucagon receptor as well as several key hepatic enzymes, such as peroxisome proliferator-activated receptor gamma, glucose-6-phosphatase, and phosphoenolpyruvate carboxykinase, was altered in malnourished animals. Finally, liver glycogen mobilization in response to fasting and the ability of exogenous glucagon to raise plasma glucose levels were lower in LP mice. Therefore, chronic protein malnutrition leads to several alterations in both the alpha-cell function and hepatic glucagon signaling. (Endocrinology 153: 1663-1672, 2012)